2011
DOI: 10.5012/bkcs.2011.32.8.2771
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Electrode by PEDOP with MWCNTs-Palladium Nanoparticles for the Determination of hydroquinone and Catechol

Abstract: Poly-ethylenedioxypyrrole (PEDOP) coated thiolated multiwall carbon nanotubes palladium nanoparticles (MWCNTs-Pd) modified glassy carbon electrode (GCE) [PEDOP/MWCNTs-Pd/GCE] for the determination of hydroquinone (HQ) and it's isomer catechol (CA) were synthesized and compared with bare GCE and thiolated multiwall carbon nanotubes (MWCNTs-SH/GCE). The modification could be made by simple processes on a GCE with MWCNTs-Pd covered by PEDOP in a 0.05 M tetrabutylammonium perchlorate (TBAP)/MeCN solution system. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The limit of detection is calculated to be 6.3 pM based on 3 times the standard deviation (s) of the blank value. The reported detection limit was found to be the lowest when compared to the previously reported catechol electrochemical sensors (TableS3of ESI †) [40][41][42][43][44][45][46][47][48][49][50][51][52]. The wider calibration range and low detection limits may be attributed to higher surface area, stability and catalytic effects (in the presence of Cu 2+ ) of the AuAC/PEDOT/Au nanocomposite.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The limit of detection is calculated to be 6.3 pM based on 3 times the standard deviation (s) of the blank value. The reported detection limit was found to be the lowest when compared to the previously reported catechol electrochemical sensors (TableS3of ESI †) [40][41][42][43][44][45][46][47][48][49][50][51][52]. The wider calibration range and low detection limits may be attributed to higher surface area, stability and catalytic effects (in the presence of Cu 2+ ) of the AuAC/PEDOT/Au nanocomposite.…”
mentioning
confidence: 88%
“…The reported detection limit was found to be the lowest when compared to the previously reported catechol electrochemical sensors (Table S3 of ESI †). [40][41][42][43][44][45][46][47][48][49][50][51][52] The wider calibration range and low detection limits may be attributed to higher surface area, stability and catalytic effects (in the presence of Cu 2+ ) of the AuAC/PEDOT/Au nanocomposite. The reproducibility of the developed sensor was measured at 10 À9 M and the relative standard deviation (RSD) was found to be 1.23% for three successive measurements using the developed sensor and found to be stable for 1 week when stored dry at room temperature.…”
Section: Mechanismmentioning
confidence: 99%
“…It is necessary to compare the LOD, linearity and other properties of the proposed composite electrode with the other published works (Table ) . The lowest LOD with a good linear range was obtained at Pd/Poly(TAU)/GCE when compared to the reported studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, used to modify electrodes, CNTs typically become entangled, and form kinks that work against electron transfer. However, CNTs loaded with metal particles such as Pd [8], Au [9] and Ag [10] can dramatically improve electronic transmission speeds. De Luca et al [11] reported the hydrogen‐sensing properties of Pt/TiO 2 /MWCNT composites.…”
Section: Introductionmentioning
confidence: 99%